2011
DOI: 10.1371/journal.pone.0016837
|View full text |Cite
|
Sign up to set email alerts
|

NIH Disease Funding Levels and Burden of Disease

Abstract: BackgroundAn analysis of NIH funding in 1996 found that the strongest predictor of funding, disability-adjusted life-years (DALYs), explained only 39% of the variance in funding. In 1998, Congress requested that the Institute of Medicine (IOM) evaluate priority-setting criteria for NIH funding; the IOM recommended greater consideration of disease burden. We examined whether the association between current burden and funding has changed since that time.MethodsWe analyzed public data on 2006 NIH funding for 29 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
203
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(213 citation statements)
references
References 18 publications
4
203
3
1
Order By: Relevance
“…However, in the United States, a mismatch between National Institutes of Health funding and burden of disease has persisted despite 1998 Institute of Medicine recommendations to improve funding priorities. 6,7 Many of the diseases in less developed countries have a substantial prevalence in more developed countrieswhere they are well studied, raising the question of whether the best strategy would be to apply evidence derived from trials conducted in more developed nations to populations in less developed countries and vice versa. 18 The determinants of disease as well as the contexts for prevention and treatment are sometimes similar, but other times they can be vastly different in low-and middleincome countries, limiting the adoption of recommendations developed in highincome settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the United States, a mismatch between National Institutes of Health funding and burden of disease has persisted despite 1998 Institute of Medicine recommendations to improve funding priorities. 6,7 Many of the diseases in less developed countries have a substantial prevalence in more developed countrieswhere they are well studied, raising the question of whether the best strategy would be to apply evidence derived from trials conducted in more developed nations to populations in less developed countries and vice versa. 18 The determinants of disease as well as the contexts for prevention and treatment are sometimes similar, but other times they can be vastly different in low-and middleincome countries, limiting the adoption of recommendations developed in highincome settings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that funding from the National Institutes of Health for all patient populations in the United States is only modestly correlated with the burden of disease. 6,7 However, it is unknown how well existing pediatric clinical trials are aligned with the needs of children, both in high-income countries and globally. Clinical trials have been previously used as a proxy of clinical research activity in comparisons of research and disease burden.…”
mentioning
confidence: 99%
“…This skewed resource allocation is particularly pronounced in the orthopaedic literature where increased global musculoskeletal disease and trauma in the developing world have not been met with a concomitant increase in attention or funding [2,17,30]. Research is a way to contribute lasting change in a lowresource setting and is as important as research performed in a high-resource setting.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is growing interest in the investigation of multidimensional effects of COPD, there has been little research addressing the impact of COPD on disability (30). Disability, or even its descriptors such as ADLs or IADLs, is an infrequent outcome in COPD studies (31), and representative national data have rarely been used to test the impact of COPD on any form of disability (11).…”
Section: Discussionmentioning
confidence: 99%